Assessment of soil erosion vulnerability in the souk ahras region - Aya Errahmane Mahdi (My University, 2026)
Soil erosion is one of the major environmental challenges affecting Mediterranean regions, particularly in northern Algeria due to the conjunction of several factors such as climate, soil characteristics, and topography. This study applies the Revised Universal Soil Loss Equation (RUSLE) integrated with GIS to assess soil loss rates and identify erosion-prone areas in Souk Ahras province in northern Algeria. Results indicate that the mean annual soil loss for the province is 2.61 t·ha⁻¹·yr⁻¹, which is below the Maghreb’s tolerable threshold of 7 t·ha⁻¹·yr⁻¹. However, spatial modeling reveals that 4% of the basin faces high to very high susceptibility, with localized erosion rates reaching up to 80.08 t·ha⁻¹·yr⁻¹. These "hotspots" are predominantly located in the northern and northeastern mountainous sectors, driven by the convergence of steep slopes (LS values up to 36.48) and intense rainfall aggressiveness (R values up to 288.11 MJ·mm/ha·hr·yr). The generated maps serve as a decision-support tool for local authorities to prioritize conservation strategies including reforestation and contour farming to protect strategic infrastructure dams. ----------------------------------------------------------------------- يُعد انجراف التربة أحد أكبر التحديات البيئية التي تؤثر على مناطق البحر الأبيض المتوسط، وخاصة في شمال الجزائر، نتيجة لتضافر عدة عوامل مثل المناخ وخصائص التربة والتضاريس. طبقت هذه الدراسة المعادلة العالمية المعدلة لفقدان التربة (RUSLE) المدمجة مع نظم المعلومات الجغرافية (GIS) لتقييم معدلات فقدان التربة وتحديد المناطق الأكثر عرضة للانجراف في ولاية سوق أهراس بشمال الجزائر. أظهرت النتائج أن متوسط فقدان التربة السنوي على مستوى الولاية يبلغ 2.61 طن·هكتار⁻¹·سنة⁻¹، وهو أقل من العتبة المسموح بها في المغرب العربي والتي تقدر بـ 7 طن·هكتار⁻¹·سنة⁻¹. إلا أن النمذجة المكانية كشفت أن 4% من الولاية تتعرض لدرجة عالية إلى عالية جداً من القابلية للانجراف، حيث تصل معدلات التآكل الموضعية إلى 80.08طن·هكتار⁻¹·سنة⁻¹. تتمركز هذه "البؤر الساخنة" بشكل رئيسي في القطاعات الجبلية الشمالية والشمالية الشرقية، مدفوعة بتقاطع المنحدرات الشديدة (قيم عامل الطول والانحدار LS تصل إلى 36.48) مع عدوانية أمطار غزيرة (قيم عامل R تصل إلى 288.11 ميجاجول·مم/هكتار·ساعة·سنة. تُعد الخرائط المنتجة أداة داعمة للقرار بالنسبة للسلطات المحلية لتحديد أولويات استراتيجيات الحفظ – بما في ذلك إعادة التحريج والزراعة الكنتورية – لحماية البنية التحتية الاستراتيجية المتمثلة في السدود -------------------------------------------------------------------- L’érosion des sols constitue l’un des principaux défis environnementaux affectant les régions méditerranéennes, en particulier le nord de l’Algérie, en raison de la combinaison de plusieurs facteurs tels que le climat, les caractéristiques des sols et la topographie. Cette étude applique l’Équation Universelle Révisée des Pertes en Sol (RUSLE), intégrée à un Système d’Information Géographique (SIG), afin d’évaluer les taux de perte en sol et d’identifier les zones vulnérables à l’érosion dans la wilaya de Souk Ahras, au nord de l’Algérie. Les résultats indiquent que la perte moyenne annuelle en sol pour la province est de 2,61 t·ha⁻¹·an⁻¹, une valeur inférieure au seuil de tolérance du Maghreb fixé à 7 t·ha⁻¹·an⁻¹. Toutefois, la modélisation spatiale révèle que 4 % du bassin présentent une susceptibilité élevée à très élevée à l’érosion, avec des taux localisés pouvant atteindre 80,08 t·ha⁻¹·an⁻¹. Ces « points chauds » sont principalement situés dans les secteurs montagneux du nord et du nord-est, sous l’effet combiné de fortes pentes (valeurs LS jusqu’à 36,48) et d’une agressivité pluviométrique élevée (valeurs R jusqu’à 288,11 MJ·mm/ha·h·an). Les cartes produites constituent un outil d’aide à la décision destiné aux autorités locales pour hiérarchiser les stratégies de conservation, notamment le reboisement et l’agriculture en courbes de niveau, afin de protéger les infrastructures stratégiques telles que les barrages.
Keywords: Soil Erosion; RUSLE; GIS; Souk Ahras; Rainfall aggressiveness; Dams.; انجراف التربة، نظم المعلومات الجغرافية، سوق أهراس،; NDVI; Érosion des sols; SIG; agressivité des précipitations; barrages.